Quantifying and managing food-sourced nutrient metabolism in Chinese cities. (September 2016) - Lin, Tao; Wang, Jin; Bai, Xuemei; Zhang, Guoqin; Li, Xinhu; Ge, Rubing; Ye, Hong
Abstract: Food supply and consumption are critical for sustaining urban system functions, and are key determinants of the quantity and pathways of nutrient flow in cities. Nutrient elements from urban food consumption are becoming major pollutant sources in urban environments. Therefore, understanding flow magnitude and pathways, the role of a growing population, and changing dietary structure and technology in future nutrient metabolism are essential to understand cities as ecosystems and urban environmental management. Taking the city of Xiamen, a rapid urbanizing area of Southeast China as a case study, we simulated urban metabolism of three major food-sourced nutrient elements (carbon, nitrogen, and phosphorus or CNP) over 1991–2010 and environmental emissions. Impacts of future population growth, dietary habit change, and waste treatment improvement on various environments were forecast by scenario analysis. A sensitivity analysis was conducted to test how different waste treatment technologies affect environmental emissions from food-sourced nutrients. Our results show that the food-sourced CNP had various metabolic fluxes through urban systems, with carbon mostly emitted into the air and nitrogen and phosphorus mostly discharged into landfills and water. Population growth and dietary structure change will accelerate increases of nutrient emissions to the environment, whereas enhancing current waste treatment technology can just alter emissions to different environments. Based on the results, we discuss how food-sourced nutrient metabolism can be better managed, to enhance connectivity between cities and their hinterlands and maintain environmental emissions within the carrying capacity of the cities. Highlights: Material flow analysis quantifies food-sourced nutrient urban metabolism (FSNUM). Scenario analysis simulates possible future environment emissions. Sensitivity analysis helps to control environmental impacts of FSNUM. Presents the whole urban food-sources nutrient metabolism and its futures Helps to manage the urban food-sourced nutrient discharging amount